2000
DOI: 10.1007/s002100000281
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity at the β 2 -adrenoceptor on macrophages is a major determinant of the anti-inflammatory effects of β 2 -agonists

Abstract: Previous research has shown that beta-adrenoceptor (beta-AR) agonists have potent anti-inflammatory capabilities, e.g. represented by suppression of release of the proinflammatory cytokines. Aim of this research was to determine whether the effects of beta-agonists on LPS-induced TNFalpha and IL-10 release are influenced by their different stereochemistry. In addition, the role of the beta-AR subtypes was studied. The effect of two stereoisomers of the selective beta2-AR agonist TA2005 [(R,R)- and (S,S)-] on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
2
20
1
Order By: Relevance
“…This observation clearly indicated that the effects of clenbuterol on systemic cytokine concentrations are mediated via the b 2 -AR, which is in accordance with previous in vitro findings [15,17,19].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This observation clearly indicated that the effects of clenbuterol on systemic cytokine concentrations are mediated via the b 2 -AR, which is in accordance with previous in vitro findings [15,17,19].…”
Section: Discussionsupporting
confidence: 81%
“…In vitro studies on the mechanism of action at cellular level, not only showed a selective effect through the b 2 -AR but also an increase in intra-cellular cAMP, comparable to levels induced by phosphodiesterase-IV inhibitors. Based on comparative studies between b 2 -AR agonists in our laboratories we selected clenbuterol as the most active and potent agent in the current experimental setup [e. g. 17,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AEA, N-(2-hydroxyethyl-1,1,2,2-d 4 )-(5Z,8Z,11Z,14Z)-eicosatetraenamide, 2-AG, (5Z,8Z,11Z,14Z)-eicosatetraenoic acid, 2-glycerol-1,1,2,3,3-d 5 ester, palmitoylethanolamide (PEA), Cell Culture-Human monocytic leukemia U937 cells were purchased from American Type Culture Collection (Manassas, VA) and were grown in RPMI 1640 medium supplemented with 10% fetal bovine serum, 1 g/ml fungizone (amphotericin B), 100 units/ml penicillin, 100 g/ml streptomycin, and 2 mM L-glutamine (all from Invitrogen). The U937 monocytic cells were differentiated into macrophages using 2 ng/ml phorbol 12-myristate 13-acetate (PMA; Sigma) for 48 h, according to standard procedures (42)(43)(44). Cells were grown in a humidified incubator at 37°C and 5% CO 2 at 37°C in humidified 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…ISO and IBMX; Safrany and Shears, 1998) have been tested on orthovanadate-induced NO production in J774A.1 cells. As macrophages bear β2-adrenergic receptors (Izeboud et al, 2000), and isoproterenol is a potent superoxide anion and hydrogen peroxide scavenging agent, we expected the inhibition of NO production of VO 4 or rutin + VO 4 induced J774A.1 cells. (Koncz and Horváth, 2000).…”
mentioning
confidence: 99%